2005
DOI: 10.1590/s1415-43662005000400008
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial de propriedades de Latossolo e da produção de café em diferentes superfícies geomórficas

Abstract: Com o objetivo de avaliar a variabilidade espacial de propriedades do solo e produção de café em diferentes Superfícies Geomórficas (SG) na região do Alto Paranaíba, MG, instalaram-se duas malhas de 200 x 850 m com intervalos regulares de 50 m, com 68 pontos amostrais cada uma, sob cultivo de café. As amostras de solo foram coletadas na profundidade de 0-0,20 m, nos pontos de intercessão dessas malhas. A produção de café foi avaliada em duas colheitas de grãos em coco das plantas mais próximas da intercessão d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 18 publications
(17 reference statements)
4
13
0
11
Order By: Relevance
“…This wide data range is due to fertilizer application in rows and for P, due to its low mobility in the soil. Similar results were observed by SANCHEZ et al (2005) andSOUZA et al (2006) in areas cultivated with coffee and sugarcane, respectively.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This wide data range is due to fertilizer application in rows and for P, due to its low mobility in the soil. Similar results were observed by SANCHEZ et al (2005) andSOUZA et al (2006) in areas cultivated with coffee and sugarcane, respectively.…”
Section: Resultssupporting
confidence: 85%
“…SANCHEZ et al (2005) studied the influence of geomorphic surfaces in the spatial variability of soil properties and found that small variations in the gradient led to different terrain variability in relation to chemical and texture properties, in which the spatial variability was higher in older and flat surfaces, that was reflected in the spatial variability of coffee production areas. The adjusted semivariogram model parameters shown in Table 2 were used to estimate values at unsampled locations by kriging (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results obtained, in agreement with Souza et al (2003) and Sanchez et al (2005), it is verified that, through the kriging maps, it is possible to obtain information that enable a better understanding of the spatial distribution pattern and a definition of the handling and collection zones of coffee seeds with higher physiologic quality, factors that may interfere in the plantation's production. Knowledge on the spatial variability of soil and plant properties that control crop yields is indispensable in modern agriculture, since minor changes can lead to great yield differences (Silva et al, 2010b).…”
Section: Variablessupporting
confidence: 86%
“…As informações obtidas por meio do mapeamento da variabilidade dos atributos dos solos são utilizadas no planejamento das práticas de manejo para conservação do solo e da água (Mello et al, 2006;Silva et al, 2008;Sanchez et al, 2009;Vaezi et al, 2010), produção de culturas agrícolas (Sanchez et al, 2005;Siqueira et al, 2010b;Mann et al, 2010), estudos relacionados à gênese (Camargo et al, 2008a), otimização amostral (Montanari et al, 2005), emissão de CO 2 (Panosso et al, 2009;La Scala Júnior et al, 2010;Brito et al, 2010;Mendonça et al, 2011;Merbold et al, 2011). Pode-se identificar, por meio deste mapeamento, áreas com maior homogeneidade dos atributos dos solos.…”
Section: Introductionunclassified